Sources of primary production to Arctic bivalves identified using amino acid stable carbon isotope fingerprinting*. Issue 4 (4th July 2019) - Rowe, Audrey G.; Iken, Katrin; Blanchard, Arny L.; O'Brien, Diane M.; Døving Osvik, Renate; Uradnikova, Martina; Wooller, Matthew J.
ABSTRACT: Benthic invertebrates are a crucial trophic link in Arctic marine food webs. However, estimates of the contribution of different primary production sources sustaining these organisms are not well characterised. We measured the stable carbon isotope values ( δ 13 C) of essential amino acids (EAAs) in muscle tissue from two common bivalve genera ( Macoma spp. and Astarte spp.) collected in Hanna Shoal in the northeastern Chukchi Sea. Mixing models comparing the δ 13 CEAA fingerprints of the bivalves to a suite of primary production endmembers revealed relatively high contributions of EAAs from phytoplankton and bacteria in both species. We also examined whether δ 13 CEAA fingerprints could be produced from the EAAs preserved in bivalve shells, which could allow primary production sources to be estimated from ancient bivalve shells. The δ 13 CEAA fingerprints from a suite of paired modern bivalve shells and muscle from Macoma calcarea from across the Chukchi Sea revealed a correspondence between the estimates of the dominant primary production source of EAAs derived from analyses of these two tissue types. Our findings indicate that δ 13 CEAA fingerprinting of marine bivalves can be used to examine dominant organic matter sources in the Arctic marine benthos in recent years as well as in deeper time.